2016
DOI: 10.1007/s00464-016-4758-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of the vascular arrangement including the inferior mesenteric artery and left colic artery in laparoscope-assisted colorectal surgery

Abstract: The present 3D reconstruction technique was useful for determining the 3D vascular anatomical pattern including the relative positions of the IMA, SCA, and IMV during laparoscope-assisted left-side colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 15 publications
5
35
0
7
Order By: Relevance
“…Hirai et al [ 3 ] clarified the anatomic relationship among the ICA, RCA and SMV using 3D images. We also applied 3D imaging during LACS [ 11 ]. The reconstructed 3D image could easily be observed from any angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hirai et al [ 3 ] clarified the anatomic relationship among the ICA, RCA and SMV using 3D images. We also applied 3D imaging during LACS [ 11 ]. The reconstructed 3D image could easily be observed from any angle.…”
Section: Discussionmentioning
confidence: 99%
“…After predicting the direction of laparoscopic observation of the abdominal organs, a 3D image can be reconstructed for the field of view of the laparoscope [ 19 ]. Our prior study, which involved the use of 3D images, demonstrated that left coronary artery (LCA) branching patterns could be classified into three groups and that the specific distances from the inferior mesenteric artery (IMA) to the LCA branch and the inferior mesenteric vein (IMV) did not significantly differ across these three groups [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear understanding of the vascular anatomy of the IMA and inferior mesenteric vein (IMV) is essential for this low-tie procedure. However, there are multiple types of branch vessels originating from the IMA that makes this surgical procedure technically demanding[ 6 ]. We studied the vascular anatomy of the IMA to safely and effectively dissect the lymph nodes around the IMA while preserving the LCA in a laparoscopic procedure for rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior mesenteric artery (IMA) has different branching pattern. Since Latarjet's classification of 1949, many authors, even when using volume‐rendered 3D‐CT, have tried to preoperatively assess the vascular anatomy of the IMA . In summary, three different patterns, types I, II and III, have been described.…”
mentioning
confidence: 99%